Development of The For See Four Si Method To Improve Pedagogical Competence of Early Childhood Teachers in The Mapanget District Manado City - Saroinsong, Nola Melda; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study aims to develop the For See Four Si method to improve the pedagogical competence of Early Childhood Education (PAUD) teachers in the PKG, Mapanget District, Manado City. This study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research location was conducted at the PKG, Mapanget District, Manado City, involving PAUD teachers as samples in the study. Data were obtained through interviews, observations, expert validation tests, feasibility and effectiveness tests in the field. The results of the analysis showed that many teachers experienced obstacles in integrating ICT in learning, which impacted the effectiveness of teaching. After the implementation of the For See Four Si Method, a significant increase was found in the pedagogical competence of teachers, especially in the aspects of curriculum preparation, ICT use, and learning evaluation. The results of the study showed that the pedagogical competence of PAUD teachers in general had an average score of 60.23. This indicates that PAUD teachers have a basic understanding of pedagogical competence, but there is still room for improvement, especially in the aspects of mastery of learning theory, curriculum development, and ICT use. And the results of the summary of the assessment or validation carried out by experts produced an overall average score of 88% with the category Very Suitable for use in improving the pedagogical abilities of PAUD Teachers.